Evaluating the Safety of Intraoperative Antiarrhythmics in Pediatric Cardiac Surgery Patients - Beaty, Rachel S.; Moffett, Brady S.; Hall, Stuart; Kim, Jeffrey (Pediatric cardiology, 2015)
Cardiac arrhythmias occurring during the intraoperative period for cardiac surgery have been associated with excess morbidity and mortality. Several antiarrhythmics have been utilized for the management of intraoperative arrhythmias. These antiarrhythmic medications can cause undesirable adverse outcomes in the intensive care setting. The incidence and treatment of adult intraoperative arrhythmias have been studied. In addition, the prevalence, risk factors, and optimal treatment of pediatric postoperative arrhythmias have also been studied. However, the literature has not been published on intraoperative antiarrhythmia treatment during pediatric cardiac surgery. The purpose of this study was to determine the safety of intraoperative antiarrhythmic medications utilized in pediatric cardiac surgery patients. This was a retrospective review of all patients who received an intraoperative antiarrhythmic in the cardiovascular operating room at Texas Children’s Hospital. Patients were included if they underwent cardiovascular surgery from November 2008 to July 2013 and were excluded if antiarrhythmics were given intraoperatively for other indications (i.e., esmolol for hypertension) or if patients were older than 18 years of age. Safety of antiarrhythmic treatment was determined by the absence or presence of adverse events. Control or recurrence of the arrhythmia was analyzed as a secondary measure to help determine antiarrhythmic efficacy. A total of 45 patients were identified (53.3 % male). Patients were a median of 0.52 years at the time of surgery. Primary surgery types were tetralogy of Fallot repair ( n = 6; 13.3 %) and ventricular septal defect closure ( n = 5, 11.1 %). Thirty-one patients (68.9 %) had documented adverse events after the administration of antiarrhythmics. Most of these adverse events occurred after the administration of amiodarone ( n = 16; 51.6 %) followed by esmolol ( n = 15; 48.4 %). Fifty-one percent of the arrhythmias resolved in the operating room ( n = 23), and nearly half ( n = 19) of all patients were discharged home on an antiarrhythmic medication. A high incidence of adverse events was associated with intraoperative administration of antiarrhythmic medications.